(untitled) (GIST – Education and Learning Research Journal, 2014)
The present study investigated how fifteen Iranian EFL learners developed the ability to self-assess their writings through having access to the rater’s scores. The participants were supervised for four weeks as they went through their first experience in self-assessment. They were provided with a detailed evaluation sheet for assessing their work, and after each self-evaluation they were able to have access to the teacher-assigned scores. The results indicated a high correlation between self-assessment and teacher-assessment. It was revealed that students’ self-assessment throughout the study turned out to be highly correlated with the teacher-assessment. It was also shown that the learners assessed different components of their writing in a manner comparable to that of the teacher. The findings confirmed that self-assessment could not only be viewed as a useful tool for evaluating learners’ performance but also be regarded as an efficient instrument for developing their writing skill.